AI in Green Marketing: Promoting Sustainable Consumer Choices Through Artificial Intelligence (Journal of Asian Development Studies, 2025)
This paper examines the role of artificial intelligence (AI) in improving green marketing strategies to drive sustainable consumer decisions through personalization, transparency, and communication. It bridges the knowledge gap regarding the effects of AI-basedsystems on consumer trust, perceived usefulness, and purchase intentions, and alleviates technological anxiety, especially in emerging markets such as Pakistan. In a cross-sectional, quantitative design, the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to investigate the direct, mediating, and moderating relationships among AI-driven marketing constructs. The research assessed reliability, validity, and model fit using SmartPLS 4 with 385 respondents with experiencewith AI-based marketing tools. The findings showed that transparency and green marketing communication using AI is the most significant predictor (R2 = 0.773) of sustainable consumer choice. Consumer trust and perceived usefulness play significant roles in mediating these relationships, whereas technological anxiety does not. The arguments are supported by the findings that AI is a technological and behavioral attacker of encouraging sustainability. The study is an expansion of the Resource-Based View (RBV) and the Technology Acceptance Model (TAM), as it frames AI as an ethical strategic asset that can fill the gap between digital innovation and environmental responsibility, providing practical recommendations on how AI can be used to sustain marketing activities and AI policy development.